Experience report: Use of play material to awareness the population in primary case (Research, Society and Development, 2022)
The use of recreational activities aimed at raising awareness among users of the public health service in Primary Care acts fundamentally to improve eating habits and healthier choices, bringing a better quality of life to the population. In this sense, the use of recreational materials in the Basic Health Unit (BHU) as a way of spreading knowledge has a preventive effect on health, preventing the development of chronic non-communicable diseases and encouraging greater participation of health professionals. Therefore, the study in evidence aims to report the experience of students in the 1st semester of the Medicine course in the elaboration of a project aimed at good health practices, from the stimulus to healthy eating. To carry out the activity, a blood vessel made of biscuit, fat molecules, which could be added or removed from the vessel, and photographs of healthy foods and harmful foods were used as play material. This dynamic was intended to allude to the negative and positive effects of these foods. In this way, the activity carried out with the biscuit blood vessel was extremely well received by the population and very well performed by the group of students, allowing doubts to be resolved and direct contact with the community to be established. In this sense, the activity was of great importance for the outline of academic and professional life for the students of the first semester of Medicine who participated in this action.